Survei pemahaman siswa SMA dan SMK Di Balikpapan Kota terhadap mitigasi bencana tanah longsor - Tiara Mustika Mawardah; Muhamad Zen Alhabsy Suneth; Rifqi Gandhie Pratama Husni Putra; Alif Athallah Ramadhani; Andi Marini (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2025)
Landslide is the process of moving rock mass (soil) due to gravity. Landslide occurs due to disturbance of equilibrium of forces acting on the slope, i.e. retaining force and launching force. Balikpapan City has a slope between 15-40%, with an area of 21,305.57 hectares or 42.33% of the total area.  Balikpapan City is classified as an area that rarely experiences landslides. However, several landslide incidents have been reported, so people are encouraged to remain vigilant and take preventive measures.  The aim of this study is to focus on the potential landslide hazard in Balikpapan City and how to mitigate it. Because Balikpapan city has hilly contours with soil types that are easily eroded. The method used in this research is the distribution of questionnaires distributed using Google Form link and sent to 7 schools in Balikpapan city.  Data collection started on 6 November 2024.  The results of this data collection activity include 7 high school/vocational school and Madrasah located in Balikpapan City with a total of 490 respondents, by being given 10 questions containing landslide disaster, it is found that the results of ‘agree’ get the most results in the answers of high school students with an average of 90% each school. With this it can be said that students of SMK and Madrasah know and understand about landslides and are familiar with the causes and impacts of landslides. The contribution given in this research includes a number of crucial steps to improve the understanding and awareness of SMA and SMK students in Balikpapan City about landslide disaster. With these contributions, the research is expected to have a positive effect on increasing the awareness and knowledge of SMA and SMK students in Balikpapan City on the importance of landslide disaster mitigation. The findings provide valuable insights for relevant institutions in addressing landslide disaster mitigation efforts.